Bidirectional Causal Associations Between Inflammatory Bowel Disease and Ankylosing Spondylitis: A Two-Sample Mendelian Randomization Analysis - Cui, Zhiyong; Hou, Guojin; Meng, Xiangyu; Feng, Hui; He, Baichuan; Tian, Yun (Frontiers in Genetics, 2020)
Background: Associations between inflammatory bowel disease (IBD) (including ulcerative colitis (UC) and Crohn’s disease (CD)) and ankylosing spondylitis (AS) were discovered in observational studies, but no evidence supported the causal relationship between the two diseases. Methods: We employed two-sample Mendelian randomization (MR) to estimate the unconfounded bidirectional causal associations between IBD (including UC and CD) and AS. We selected single nucleotide polymorphisms (SNPs) from genome-wide association studies (GWAS) after strictly assessing the quality of the studies in the IEU GWAS database. Sensitivity analyses were also conducted to verify whether heterogeneity and pleiotropy can bias the MR results. Results: We found positive causal effects of genetically increased UC, CD and IBD risk on AS (e.g., UC and AS, IVW OR: 1.0256, 95% CI: 1.0130~1.0385, p=6.43E-05). However, we did not find significant causal associations of AS with UC, CD or IBD (e.g., AS and UC, IVW OR: 1.1858, 95% CI: 0.8639~1.6278, p=0.2916). The sensitivity analysis also confirmed that horizontal pleiotropy was unlikely to bias the causality (e.g., UC and AS, MR-Egger: intercept p=0.1326). The leave-one-out analysis also demonstrated that the observed links were not driven by single SNP. No evidence of heterogeneity was found between the genetic variants (e.g., UC and AS, MR-Egger: Q statistic= 43.1297, I2＜0.0001, p=0.7434). Conclusions: Our results provide new evidence indicating there are positive causal effects of IBD on AS in the European population. We suggest that the features of inflammatory bowel disease in particular should be assessed in the diagnosis of ankylosing spondylitis. We also provide some advice for preventing and treating the two diseases.